Brassinosteroid Signaling Converges With Auxin-Mediated C3H17 to Regulate Xylem Formation in Populus - Tang, Xianfeng; Wang, Congpeng; Liu, Yu; He, Guo; Ma, Nana; Chai, Guohua; Li, Shengjun; Xu, Hua; Zhou, Gongke (Frontiers in Plant Science, 2020)
Brassinosteroid (BR) signaling has long been reported to have an effect on xylem development, but the detailed mechanism remains unclear, especially in tree species. In this study, we find PdC3H17, which was demonstrated to mediate xylem formation driven by auxin in our previous report, is also involved in brassinosteroid-promoted xylem development. Y1H analysis, EMSA and transcription activation assay confirmed that PdC3H17 was directly targeted by PdBES1, which is a key transcriptional regulator in BR signaling. Tissue specificity expression analysis and in situ assay revealed that PdC3H17 had an overlapping expression profile with PdBES1. Hormone treatment exams verified that xylem phenotypes in PdC3H17 transgenic plants, which were readily apparent in normal condition, were attenuated by treatment with either brassinolide (BL) or the BR biosynthesis inhibitor propiconazole (PCZ). The subsequent qRT-PCR analyses further revealed that BR converged with PdC3H17 to influence transcription of downstream xylem related genes. Additionally, the enhancement of xylem differentiation by auxin in PdC3H17 overexpression plants was significantly attenuated compared with wild-type and dominant negative plants due to BR deficiency, which suggested that the BR- and auxin-responsive gene PdC3H17 acted as an mediation of these two hormones to facilitate xylem development. Taken together, our results demonstrate that brassinosteroid signaling converges with auxin-mediated PdC3H17 to regulate xylem formation in Populus, and thus provide insight into the regulation mechanism of BRs and the crosstalk with auxin signaling on xylem formation.